Rwanda Climate Services for Agriculture: Qualitative Evaluation through a Gender Lens - Gumucio, Tatiana; Hansen, James; Nsengiyumva, Gloriose; Birachi, Eliud Abucheli; Kagabo, Desire; Rose, Alison; Munyangeri, Yvonne (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This report presents results from a qualitative evaluation of the Rwanda Climate Services for Agriculture project, carried out in October of 2019. The project focused on enhancing smallholder farmer resilience and ability to cope with climate variability through interventions such as Participatory Integrated Climate Services for Agriculture (PICSA) and Radio Listeners’ Clubs (RLC). Recognizing that gender-related factors influence farmers’ capacities to access, use, and benefit from climate information, the evaluation critically analyzed differences and trends in women’s and men’s access to weather and climate information, use of the information in their farm and non-farm livelihood decision-making, and benefit from their climate-informed decisions made. The project also sought to reach increasing numbers of farmers over the course of its duration, starting with pilot districts and extending interventions into additional areas over its four years. Consequently, the evaluation took into account a farmer’s length of exposure to one or multiple project interventions, sampling farmers representing “treatment categories” of participation in: i) PICSA in 2016, ii) PICSA in 2018, iii) PICSA and participating in a RLC, and iv) not having participated in either intervention.